2006
DOI: 10.1088/0268-1242/21/8/025
|View full text |Cite
|
Sign up to set email alerts
|

Influence of annealing on physical properties of evaporated SnS films

Abstract: The effect of annealing on the composition, crystal structure, surface features and electro-optical properties of tin mono-sulfide (SnS) films, deposited by thermal evaporation at 300 • C, has been studied. Elemental analysis of the films shows sulfur deficiency, which increases at higher annealing temperatures (T a). The SnS structure in the as-deposited and annealed films remains orthorhombic. With an increase in T a , the grain size and the surface roughness are reduced. The electrical resistivity also decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
34
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(45 citation statements)
references
References 27 publications
(30 reference statements)
10
34
1
Order By: Relevance
“…It was found that the activation energy values decreases with increase in precursor concentration up to 0.2 M and then increases for the further increase in precursor concentrations. The decrease in activation energy with the increase in precursor concentration may be attributed to the change in the electronic structure corresponding to the increase in thickness values [44]. These values suggest that the deep donor levels in lower precursor concentrations change to shallow donor levels for higher precursor concentrations in accordance with the results in the literature [6,45].…”
Section: Electrical Propertiessupporting
confidence: 85%
“…It was found that the activation energy values decreases with increase in precursor concentration up to 0.2 M and then increases for the further increase in precursor concentrations. The decrease in activation energy with the increase in precursor concentration may be attributed to the change in the electronic structure corresponding to the increase in thickness values [44]. These values suggest that the deep donor levels in lower precursor concentrations change to shallow donor levels for higher precursor concentrations in accordance with the results in the literature [6,45].…”
Section: Electrical Propertiessupporting
confidence: 85%
“…These Sn vacancies are characteristics of IV-VI compounds that play a significant role in establishing the p-type conductivity of these compounds. Devica et al [7] reported an activation energy of 0.26 eV for thermal evaporation SnS films, Noguchi et al [18] observed the activation energy between 0.28 eV and 0.34 eV in thermal evaporated SnS films. Lopez et al [17] reported an activation energy of 0.54 eV for sprayed SnS films.…”
Section: Resultsmentioning
confidence: 99%
“…) in the visible range [2], contain only relatively less-toxic materials, stable in slight acidic media [7] and may be used for infrared detection and solar cells application. SnS and PbS has also a good thermoelectric properties and it may became a good thermoelectric material for future applications, because of their potential use in cooling systems [8].…”
Section: /Snmentioning
confidence: 99%
“…Elements such as tin and sulfur are abundantly available. Tin sulfide has been synthesized using a variety of techniques such as sputtering [127], evaporation [129], electrodeposition [130] as well as chemical routes [131]. The highest reported efficiency to date is 1.3% [132].…”
Section: Other Earth-abundant Candidatesmentioning
confidence: 99%